Positive Allosteric Modulation of the Glucagon-like Peptide-1 Receptor by Diverse Electrophiles* - Bueno, Ana B. (American Society for Biochemistry and Molecular Biology, 2016)
Therapeutic intervention to activate the glucagon-like peptide-1 receptor (GLP-1R) enhances glucose-dependent insulin secretion and improves energy balance in patients with type 2 diabetes mellitus. Studies investigating mechanisms whereby peptide ligands activate GLP-1R have utilized mutagenesis, receptor chimeras, photo-affinity labeling, hydrogen-deuterium exchange, and crystallography of the ligand-binding ectodomain to establish receptor homology models. However, this has not enabled the design or discovery of drug-like non-peptide GLP-1R activators. Recently, studies investigating 4-(3-benzyloxyphenyl)-2-ethylsulfinyl-6-(trifluoromethyl)pyrimidine (BETP), a GLP-1R-positive allosteric modulator, determined that Cys-347 in the GLP-1R is required for positive allosteric modulator activity via covalent modification. To advance small molecule activation of the GLP-1R, we characterized the insulinotropic mechanism of BETP. In guanosine 5′-3-O-(thio)triphosphate binding and INS1 832-3 insulinoma cell cAMP assays, BETP enhanced GLP-1(9–36)-NH2-stimulated cAMP signaling. Using isolated pancreatic islets, BETP potentiated insulin secretion in a glucose-dependent manner that requires both the peptide ligand and GLP-1R. In studies of the covalent mechanism, PAGE fluorography showed labeling of GLP-1R in immunoprecipitation experiments from GLP-1R-expressing cells incubated with [3H]BETP. Furthermore, we investigated whether other reported GLP-1R activators and compounds identified from screening campaigns modulate GLP-1R by covalent modification. Similar to BETP, several molecules were found to enhance GLP-1R signaling in a Cys-347-dependent manner. These chemotypes are electrophiles that react with GSH, and LC/MS determined the cysteine adducts formed upon conjugation. Together, our results suggest covalent modification may be used to stabilize the GLP-1R in an active conformation. Moreover, the findings provide pharmacological guidance for the discovery and characterization of small molecule GLP-1R ligands as possible therapeutics.